Narratives in Dispute: Anti-Racist Actions in Brazilian Museums (Cadernos de Sociomuseologia, 2025)
This article aims to demonstrate the complexity of the contemporary Brazilian museum context, which points to the existence of multiple voices and perspectives in tension, in which hegemonic, historically white and Eurocentric narratives are confronted by the stories and experiences of racialized groups, particularly the black population and indigenous peoples. These museum spaces are symbolic battlefields where different versions of history and culture are disputed and are reflected in the way objects are presented in museums. The analysis of anti-racist actions in Brazilian museums invites us to reflect on the crucial role that social technologies have, can and should play in the fight against racism in Brazil by recognizing the different versions of history, giving voice to marginalized groups and implementing concrete actions as essential steps to transform these spaces into places of memory, learning and construction of a more just and egalitarian future, and minimizing the dispute over narratives by understanding that this is the way to demonstrate the diverse life experiences of Brazilians. Keywords: Museums; Museology; Representation; Heritage; Black cultures.